1997
DOI: 10.1089/scd.1.1997.6.323
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Maturation of CD34+ Cells from Peripheral Blood and Bone Marrow in Serum-Free Culture Medium with PIXY321 and Granulocyte-Colony Stimulating Factor (G-CSF)

Abstract: Bone marrow (BM) or peripheral blood (PB) CD34+ cells were cultured for 12 days in serum-free culture medium containing PIXY321 (IL-3/ GM-CSF fusion protein) with or without periodic supplements of granulocyte-colony stimulating factor (G-CSF). The cultures were evaluated at day 12 for total cell proliferation (fold increase from day 0), neutrophil differentiation by flow cytometry, using dual staining with CD15-FITC and CD11b-PE, and morphology using Wright-Giemsa and granule staining. In cultures containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, 1 M NaOH was added daily to adjust the pH to match that of the Fed cultures after feeding. In {Not Fed} and {Not Fed + NaOH} cultures, 10 ng/mL G-CSF was added every other day to prevent depletion of G-CSF due to instability (25).…”
Section: Methodsmentioning
confidence: 99%
“…However, 1 M NaOH was added daily to adjust the pH to match that of the Fed cultures after feeding. In {Not Fed} and {Not Fed + NaOH} cultures, 10 ng/mL G-CSF was added every other day to prevent depletion of G-CSF due to instability (25).…”
Section: Methodsmentioning
confidence: 99%
“…Jilani et al (42) reported that the level of CD33 expression on CD34 ϩ cells from AML patients was similar to levels observed on CD34 ϩ cells from normal donors. The CD34 ϩ cells used as target cells in our cytotoxicity and proliferation assays were isolated from G-CSF-mobilized normal donors and were therefore primed for differentiation into the myeloid lineage (43,44). We did not observe a substantial lysis of the CD34 ϩ cells by CD33 1Y2L-CTL clone (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Use of defined media and supplements is critical for interpreting the results of experiments, improving reproducibility of studies, and allowing production of cells under good manufacturing practice (GMP) conditions for clinical applications. In many cases, however, there is a discrepancy in the outcome of hematopoietic cell cultures between cultures in serum‐free media and cultures in serum‐supplemented media regarding the concentration of supplements needed for a cellular response [58]. Previously, we found that hematopoietic growth factor (HGF)–dependent proliferation of hematopoietic progenitor cells (HPCs) in the absence of serum was suppressed by the presence of accessory bone marrow cells [9].…”
Section: Introductionmentioning
confidence: 99%